Elimination of industrial Trans Fatty Acids from the food supply chain: With a focus on India - Birendra Kumar Paliwal; Meher Wan (Food Chemistry Advances)
With the growing health concerns of Industrial Trans Fatty Acids (i-TFAs) present in food, efforts are being made to eliminate these Trans Fatty Acids (TFAs) from food chain. Even after three decades of research which linked the i-TFAs and human health, getting rid of these from food supply chain is still a dream for major countries around the globe. Countries are struggling hard to convey the related scientific findings to the common public aiming to eliminate i-TFAs from food supply chain. Government and non-government organisations throughout the globe have implemented several regulatory measures to get rid of the Industrial i-TFAs from the diet. In the case of India, removing these TFAs from the food supply chain would need a multi-sectoral, proactive effort at the consumer and production levels. The paper aims to assess and give an overview of the i-TFAs to critically analyse the elimination efforts of i-TFAs from the dietary supply chain with a focus on India. The obstacles and challenges in the elimination process of industrial Trans Fatty acids from food chain are discussed which are relevant to the developing countries like India.